Prevalence of dermatophytic infections including antifungal susceptibility pattern of dermatophytes in a tertiary care hospital - Basak, Priyam; Mallick, Bandana; Pattanaik, Swetalona (International Journal of Research in Medical Sciences, 2019)
Background: Dermatophytosis is a commonly encountered superficial fungal infection in the tropical and subtropical countries. The present study was undertaken to study the clinicomycological profile of dermatophytosis and perform antifungal susceptibility testing for the isolated dermatophytes. Methods: This is 2 years cross- sectional observational study including 433 clinically suspected cases of dermatophytoses. Skin, hair and nails were collected, subjected to direct microscopy by Potassium hydroxide (KOH) mount and culture on Sabouraud’s Dextrose Agar (SDA) with chloramphenicol and cycloheximide. Positive growth on culture media was further identified by LPCB mount, slide culture test, growth on Dermatophyte Test Medium, pigment production in corn meal agar with 1% dextrose, urease test and hair perforation test. The isolated dermatophytes were subjected to antifungal susceptibility testing by agar based disc diffusion method. Results: Out of 433 samples, fungal filaments were seen in 308 (71.1%) samples by KOH mount, 259 (59.8%) dermatophytes were isolated from culture. Males (60.5%) were more commonly affected than females (39.5%). Most common age group affected was 21-30 years. Trichophyton mentagrophytes (57.5%) was the most common isolate followed by Trichophyton rubrum (30.1%). Tinea corporis was the most common clinical presentation (52.7%) followed by Tinea unguium (14.1%). Antifungal susceptibility testing showed itraconazole as the most sensitive antifungal agent, while fluconazole was least sensitive. Conclusions: This study provides a scope for assessment of prevalence and clinicomycological profile, which could help in estimation of the problem and hence prevent spread of dermatophytoses with adequate control measures.